A new bandwidth allocation scheme for data handoff calls in cellular networks - Salamah, M; Candan, I (IEEE, 2005)
This paper focuses on how to allocate bandwidth for new and handoff data calls in cellular networks. Many schemes proposed in the literature give priority to handoff calls at the expense of blocking newly originating calls and degrading channel utilization. We introduce a novel bandwidth allocation scheme based on guard policy for data handoff calls. Accordingly, if the amount of occupied bandwidth exceeds a bandwidth threshold B-t, new calls are blocked. The novelty. of our scheme is based on observing the elapsed time of data handoff calls and according to a time threshold parameter, handoff calls can either be prioritized or treated as new calls. Compared with traditional well-known schemes, the simulation results show that our scheme achieves much better results on the handoff dropping probability, new call blocking probability, grade of service (GoS) and system utilization.
International Conference on Wireless Networks, Communications and Mobile Computing -- JUN 13-16, 2005 -- Maui, HI
Keywords: handoff scheme; simulation; time-threshold parameter; grade of service (GoS); wireless networks